Endogenous rural dynamics: an analysis of labour markets, human resource practices and firm performance - Anne Margarian; Cécile Détang-Dessendre; Aleksandra Barczak; Corinne Tanguy (SN Business & Economics, 2022)
Some rural locations in industrialized countries have experienced considerable employment growth in the last decades, while others suffer from depopulation and decline. The paper aims to contribute to the development of an evolutionary approach that allows for the identification of those often difficult-to-observe evolving factors that explain success and failure of rural locations. It also wants to show how the combined recognition of evolutionary labour market perspectives, the dynamic capability view of the firm, and human resource management (HRM) theories can serve the operationalisation of evolutionary explanations in this context. According to the derived model, apparent locational disadvantages might be compensated for by subtle, potentially self-enforcing labour market dynamics that generate opportunities for certain firms and industries. Empirically, the ideas are substantiated by means of a mediation model. The empirical analysis is based on latent class analysis and discrete choice models using data from an own survey of 200 food-processing firms in urban and rural locations of one German federal state. For these observations, our results support the idea that the exploitation of HRM opportunities may be more important for good performance in rural labour markets than the direct implementation of specific innovation modes. Investment in HRM allows rural firms in our sample to realise those gains in terms of innovation and growth offered by the creation of a stable and experienced workforce. Their focus on internal labour markets potentially generates external effects, which further encourages neighbouring firms to also invest in involved HRM measures.
Keywords: R1; J24; M5; 330; Agglomeration advantages; Innovation; Human resource management; Mediation